An intermediate region in C-terminal of phosphoprotein is required for binding to nucleocapsid of Newcastle disease virus - Ahmad Raus, Raha; Siang, Tan Wen; Ali, Abdul Manaf; Yusoff, Khatijah (Academic Journals, 2011)
The phosphoprotein (P) of paramyxoviruses plays a central role in the viral genome replication and transcription. The P either binds to the unassembled nucleocapsid (NP0) to assist in viral genomic replication or binds to assembled NP (NP-RNA or NPNC) to transcribe genome to produce the subgenomic mRNAs. In this study, the region of P that binds to NPNC was mapped. To determine the binding region, 18 N- and C-terminally truncated P mutants were synthesized by in vitro translation in rabbit reticulocytes and mixed with purified NP (NPNC). The mutants which did not bind to NP were considered as mutants and they contain deleted regions that may be involved in binding to NP. To identify the mutants that did not bind to NP, radioimmunoprecipitation and protein binding assays were used. Based on radioimmunoprecipitation analysis, it was shown that the region of P that binds to NP is located within the internal region of C-terminal half of P, from amino acids 243 to 279. In agreement with the radioimmunoprecipitation analysis, protein binding assay showed that the interactive domain was mapped to the internal region of the C-terminal half of P. However, a slightly bigger region of interactive domain (amino acids 224 to 279) was determined by the latter assay. As protein binding assay is considered as a more sensitive assay as compared to radioimmunoprecipitation assay, thus, the interactive region of P to NPNC was located within C-terminal half of P between amino acids 224 to 279.